The Determinants of Trade Credit Demand: Survey Evidence and Empirical Analysis - Salima Paul; Nick Wilson (Journal of Accounting, Business and Management (JABM), 2007)
If there is a time lapse between the transaction of delivering goods and the payment, buyers are demanding finance from non-financial firms that are not in business to provide funds to their customers but to sell goods. This paper analyses the determinants of trade credit demand, which is modelled as a function of several theories: financing, transaction cost, asymmetric information, firms business environment, and specific investment. It builds on previous studies by examining a wider range of aspects of trade credit demand namely the level of purchase on credit as well as the period companies take to pay their suppliers within and outside the agreed period. Amongst our findings, our results show that the level of credit demanded and the period are affected by the need for short-term finance and thus trade credit is used to complement and/or substitute other sources of funds.